The person-affecting claim in the discussion concerning medically assisted reproduction procedures - Gaitan, Juan Manuel (Revista Ethika+, 2024)
The controversy over the relevance of assisted procreation has many facets. This makes it difficult to conclude the discussion. This article proposes an assessment of medically assisted fertilization and surrogacy in the light of the “person-affecting claim” (Parfit, 1991). The hypothesis presented holds that personal affectation does not lead to prohibition but creates a right in the resulting child because the future right to identity cannot be ignored. To support it, the affectation of the persons involved in the process and of the unborn child is reviewed. The implications of the “non-identity problem” (Parfit, 2004) and the “best interests of the child” is also evaluated.